2015
DOI: 10.3415/vcot-14-06-0088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of locally injected autologous platelet-rich plasma on second intention wound healing of acute full-thickness skin defects in dogs

Abstract: Locally injected autologous PRP does not accelerate the healing process, but increases tissue perfusion and may promote the formation of organized collagen bundles in acute full-thickness skin defects in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…In previous study, Alsabaawe, Hom et al, have been suggested an increased of epithelialization rate and regression of acute inflammatory process in PRP treated skin wounds in rabbits during week 1 postoperative period compared to week 2 where there was no statistical differences found in epithelial thickness and inflammation stage between PRP treated wound and control. Also, they indicated that the epithelialization returned to normal texture and improvement of wound healing in term of reducing the inflammatory process [ 35 , 36 ]. On the other hand, Ahmad et al, (2012) suggested that the PRP has the potential to enhance the healing of tissue at the cellular level via the recruitment proliferation, and differentiation of cells involved in tissue regeneration [ 37 ] Moreover, Gotterbarm et al, (2006) have been reported the PRP acts as a rich source of autologous growth factors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, Alsabaawe, Hom et al, have been suggested an increased of epithelialization rate and regression of acute inflammatory process in PRP treated skin wounds in rabbits during week 1 postoperative period compared to week 2 where there was no statistical differences found in epithelial thickness and inflammation stage between PRP treated wound and control. Also, they indicated that the epithelialization returned to normal texture and improvement of wound healing in term of reducing the inflammatory process [ 35 , 36 ]. On the other hand, Ahmad et al, (2012) suggested that the PRP has the potential to enhance the healing of tissue at the cellular level via the recruitment proliferation, and differentiation of cells involved in tissue regeneration [ 37 ] Moreover, Gotterbarm et al, (2006) have been reported the PRP acts as a rich source of autologous growth factors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the forest plot in Fig 3 showed two studies with not significant negative ES [ 51 , 53 ], two studies with null ES [ 30 , 46 ], seven studies with not significant positive ES [ 42 , 44 , 45 , 50 , 52 , 56 , 58 ] and four studies with significant positive ES [ 43 , 54 , 55 , 57 ]: the exclusion of each of the studies, in the sensitivity analysis, would have no relevant effect on the overall results of the meta-analysis supporting the efficacy of PRP for primary outcome. ( Fig 4 )…”
Section: Resultsmentioning
confidence: 99%
“…This finding is associated with a moderate degree of heterogeneity. The quality of evidence obtained in the meta-analysis for the primary outcome was demonstrated by sensitivity analysis, excluding alternately each of the studies, even showing negative ES [ 51 , 53 ], null ES [ 30 , 46 ], or statistically positive ES [ 43 , 54 , 55 , 57 ]: no relevant changes occurred in the results of the meta-analysis of primary outcome, persisting in statistical agreement with the hypothesis that supports the superiority of the PRP group. The sensitivity analysis finds its own indication in the identification of potential "outlier studies".…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we designed our study as a pilot study of a clinical innovative therapy on a small number of subjects following the literature on some similar studies on new treatments in dermatology [ 26 , 32 , 33 ]. We preferred to use the “case-control” study design on the same subject to reduce the variables of clinical response and avoid confounding factors such as age, race, and gender.…”
Section: Discussionmentioning
confidence: 99%